Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Pada Produk Mie Gacoan Wilayah Surakarta Dan Sukoharjo - Prima Prihatini; Anita Oktaviana Trisna Devi (Journal Of Business, Finance, and Economics (JBFE), 2023)
The purpose of this study was to analyze the effect of Halal Awareness, price, taste, brand image, service quality, Electronic Word of Mouth, and location on consumer purchasing decisions for Gacoan Noodles in Surakarta and Sukoharjo Regions which has six branches, namely in Laweyan, Banjarsari, Solo Baru, Makamhaji, Jebres, Veteran. The number of samples in this study were 171 respondents obtained using purposive sampling. The results showed that Halal Awareness, price, taste, brand image, and service quality had no partial and insignificant effect, while Electronic Word of Mouth, and location had a partial and significant effect on on consumer purchasing decisions for Gacoan Noodles in Surakarta and Sukoharjo Regions. Halal Awareness, price, taste, brand image, service quality, Electronic Word of Mouth, and location have a simultaneous and significant effect on consumer purchasing decisions for Gacoan Noodles in the Surakarta and Sukoharjo Regions. the coefficient of determination (R Square) obtained a figure of 0.207. So it can be interpreted that purchasing decisions are 20.7% influenced by Halal Awareness, price, taste, brand image, service quality, Electronic Word of Mouth, and location and 79.3% of purchasing decisions are influenced by other variables not examined in this study.